Blood in the Borderlands : Conflict, Kinship, and the Bent Family, 1821-1920 - Beyreis, David C. (University of Nebraska Press, 2020)
"Blood in the Borderlands traces the story of the Bent family from the fur trade days of the 1820s to the death of William Bent in 1869, exploring how one family lived and negotiated within shifting economic and political alliances among multinational and multiracial interests"--